Variability of the Pechora Sea Ice Area and Its Correlation With the Barents Sea Surface Temperature According to Satellite Observations and Reanalysis - E. V. Lvova; E. V. Zabolotskikh (Лëд и снег, 2024)
Variability of the Pechora Sea ice cover and the Barents Sea surface temperature during the season from October to June in 2002–2022 (except the season of 2011/2012) was studied on the basis of satellite observations and reanalysis ERA5. Influence of the sea surface temperature on the ice cover was also analyzed but without considering the other hydrometeorological parameters. Areas of the sea ice cover characteristics were calculated using data on the sea ice closeness obtained from the Advanced Microwave Scanning Radiometer 2 measurements. To analyze the variability of sea surface temperature, we used the average daily data of the European Centre for Medium-Range Weather Forecasts ERA5 reanalysis obtained by averaging hourly data. To study the spatial and temporal variability of sea ice cover and sea surface temperature, fields of daily averaged parameters were mapped. These maps and values of areas of the sea ice cover were analyzed. This made possible to reveal regularities of development of the sea ice processes in the Pechora Sea, to calculate the general trend of the sea ice area change over the considered period of time, and to divide the Barents Sea into four sectors with significantly different average values of the sea surface temperature: southwestern, northwestern, southeastern, northeastern ones. The seasonal and interannual variabilities of the Pechora Sea ice cover and the Barents Sea surface temperature were analyzed. To study the effect of sea surface temperature in different sectors of the Barents Sea on the sea ice area, the method of statistical analysis (Pearson’s linear correlation) was used for the monthly average data and the data, averaged over the sea ice season (from October to June) with different time lags. Significant correlation coefficients were obtained only for a two-month lag. With such a lag, high values of the inverse correlation coefficients were revealed between the sea surface temperature in the southwestern (up to –0.8) and northwestern (up to –0.6) sectors of the Barents Sea and sea ice area of the Pechora Sea, while in other sectors the correlation was significantly smaller or even below the significance level.